Disharmoni Peraturan Perundang-Undangan di Bidang Agraria (Lex Jurnalica, 2013)
AbstractDisharmony (disharmony) legislation also occur because of selfishness sectoral ministries/ agencies in the planning process and the legal establishment. In the harmonization of legislation is done at the central level , according to data from the Ministry of Justice and Human Rights in 2007, has made 25 of 27 harmonized draft laws proposed (92.59 %), 92 of the 107 draft regulations proposed (85.98 %); 7 of 9 proposed draft presidential regulation (77.77 %) . In the year 2008 has been harmonized 13 draft laws , draft regulations 64 and 6 draft presidential regulation. Setting the right to land is still causing a lot of problems with respect to sectoral activities , departmental and local (regional) . In his judgment , this is the result of a mismatch between the Agraria Law arrangements with other laws , such as: minning, Forestry, Spatial Planning and Investment, as well as among the Act, for example, Forestry and Mines . Based on the description of the background above, which is the case in this study were (1) legislation collide whatever sector (disharmony) with Agraria Law and (2) What are the benchmarks for assessment disharmony? The main objective of this research is to study the impact of the implementation of various laws and regulations relating to land and give you the option to harmonize , so that the legal framework for land management in Indonesia is compatible with the constitutional mandate . Based on the above background , the formulation of the problem and research objectives as well as objects of research about " disharmony legislation in the field of agrarian " as stated above , the researches of this law depart from normative legal research.Â Keywords: disharmony, legislation, agrarianAbstrakDisharmoni (ketidakharmonisan) peraturan perundang-undangan juga terjadi karena egoisme sektoral kementerian/lembaga dalam proses perencanaan dan pembentukan hukum. Dalam harmonisasi peraturan perundang-undangan yang dilakukan di tingkat Pusat, menurut data dari Departemen Hukum dan HAM pada tahun 2007, telah dilakukan harmonisasi 25 dari 27 rancangan undang-undang yang diajukan (92,59 %); 92 dari 107 rancangan peraturan pemerintah yang diajukan (85,98 %); 7 dari 9 rancangan perpres yang diajukan (77,77 %). Pada tahun 2008 telah diharmonisasi 13 rancangan undang-undang, 64 rancangan peraturan pemerintah dan 6 rancangan peraturan presiden. Pengaturan hak atas tanah masih menimbulkan banyak persoalan sehubungan denganÂ  kegiatan sektoral, departemental maupun local (daerah). Dalam penilaiannya, hal ini terjadi akibat adanya ketidaksesuaian antara pengaturan UUPA dengan UU lainnya, seperti: Pertambanagan, Kehutanan, Penataan Ruang, dan Penanaman Modal,maupun diantara UU tersebut, misalnya Kehutanan dengan Pertambangan. Berdasarkan uraian latar belakang di atas maka yang menjadi permasalahan dalam penelitian ini adalah (1) Peraturan perundang-undangan sektor apa saja yang berbenturan (disharmoni) dengan UUPA dan (2) Apa yang menjadi tolok ukur terhadap penilaian disharmoni? Tujuan utama dari penelitian ini adalah untuk mempelajari dampak implementasi dari berbagai peraturan perundang-undangan yang terkait dengan tanah dan memberikan pilihan untuk mengharmonisasikan, sehingga kerangka legal bagi pengelolaan tanah di Indonesia kompatibel dengan amanat konstitusi. Berdasarkan atas latar belakang, rumusan masalah dan tujuan penelitian serta obyek penelitian tentang â€œDisharmoni peraturan perundang-undangan di bidang agrariaâ€Â  sebagaimana telah diuraikan tersebut di atas, dalam penelitihan hukum ini bertolak dari penelitian hukum normatif. Â Kata kunci: disharmoni, peraturan, agraria